A holding for university's students in Venice - Cristiano Chiusso (Pensa MultiMedia, 2014)
Following Winnicott's concept of holding environment on one side and considering the young not only as an age of transition to adulthood, but rather as an age with its specific needs and desires on the other side, the Regional Body supporting the Right to Higher Education in Venice offers a wide range of services between educational training, career counselling and leisure, thus covering the three basic elements of the life condition of students, with particular attention to the training for the transition to work.